Preliminary Outcomes from an Intensive Multidisciplinary Pain Program in a Veteran's Administration Hospital: A Pilot Study. (2nd October 2022) - Austin, Tara; Rogers, Randall; Hodges, Cooper B.; Kominek, Courtney; Madaffer, Nicholas; Miller, Jerry; Shigaki, Cheryl
Abstract: Chronic pain is a leading cause of lost productivity, disability payments, and health care utilization among the Veteran population. As such, there is interest in chronic pain treatments that address not only physical functioning and pain, but also psychological functioning and pain-related beliefs. One such treatment that has been explored is multidisciplinary team treatments. This pilot study aimed to determine whether a multidisciplinary treatment program for chronic pain would be effective in a sample of primarily rural-based Veterans. Seventy Veterans completed multidisciplinary chronic pain treatment, which consisted of 3–5 hours of pain related services per week for twelve weeks with providers from seven different disciplines. Veterans took standardized pre- and post-test measures of functioning, pain, pain-related beliefs, and mood. The program was highly acceptable and feasible to both Veterans and medical providers. Participants reported statistically significant improvements in average pain level following the intervention and improvements in pain related beliefs, pain-related catastrophizing, pain-related self-efficacy, mood symptoms and increased activity engagement. The program was highly acceptable to participants and feasible to a rural VA medical center, as evidenced by high completion rates. Future research is needed for cost-benefit analysis of the multidisciplinary program compared to less time-intensive pain related services (e.g. CBT-CP), post-intervention pain-related health care utilization, and the role of pain-related beliefs in treatment outcomes.